2022
DOI: 10.15294/paramita.v32i1.31048
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Web-Based Historical Sources as Learning Resources to Foster Students’ Historical Thinking Skills

Abstract: To foster students’ historical thinking in Indonesia, teachers should not merely use textbooks as the only learning resource. They must utilize primary sources in teaching history that are important to encourage students to think historically. Unfortunately, it was not easy to access primary sources in Indonesia. For that reason, this study explored alternative learning resources to overcome the main difficulty faced by history teachers in Indonesia in fostering students’ historical thinking skills. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Historical sources are also expected to arouse students' interest, making history relevant and useful for students [3][4]. Pranata et al (2019) found that incorporating multicultural values in history lessons is crucial due to the negative impact of information technology and the disintegration of unity among Indonesian youth [2].…”
Section: Indonesia Has Many Educational Institutionsmentioning
confidence: 99%
“…Historical sources are also expected to arouse students' interest, making history relevant and useful for students [3][4]. Pranata et al (2019) found that incorporating multicultural values in history lessons is crucial due to the negative impact of information technology and the disintegration of unity among Indonesian youth [2].…”
Section: Indonesia Has Many Educational Institutionsmentioning
confidence: 99%
“…As explained earlier, efforts to digitize primary sources in documents and newspapers have basically been carried out in Indonesia. Development research conducted by Widiadi et al (2022) tried to offer a website containing primary source documents to improve students' historical thinking skills. The topic raised was the Battle of Surabaya on 10 November 1945 which focused on the flag incident and the death of AWS Mallaby.…”
Section: B Historical Media Website Based On Primary Sourcesmentioning
confidence: 99%
“…In the concept of historical thinking, primary sources as teaching materials must be used so that students can have a sense of history and are not alienated from the images of the past. History teachers understand this concept, but only some apply it because some history teachers still need help accessing primary sources (Widiadi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…is HEM makes it easier for teachers to teach, especially for online learning; especially during the Covid-19 pandemic, learning requires the help of digital products. Digitizing history learning resources is "more accessible" for students (Lee, 2002) because they can access them anytime and anywhere as long as they use digital devices (Widiadi et al, 2022). In addition, it can also encourage the improvement of students' critical thinking skills through searching for much information from HEM.…”
Section: Student's Perception Of Historical Electronic Modulesmentioning
confidence: 99%